2016
DOI: 10.1371/journal.pone.0166322
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Production of IFNγ in Response to TLR7/IL-12 Stimulates Optimal B Cell Responses to Viruses

Abstract: Knowledge of the processes that underlie IgG subclass switching could inform strategies designed to counteract infections and autoimmunity. Here we show that TLR7 ligands induce subsets of memory CD4 and CD8 T cells to secrete interferon γ (IFNγ) in the absence of antigen receptor stimulation. In turn, TLR ligation and IFNγ cause B cells to express the transcription factor, T-bet, and to switch immunoglobulin production to IgG2a/c. Absence of TLR7 in T cells leads to the impaired T-bet expression in B cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 34 publications
1
43
0
Order By: Relevance
“…It is therefore tempting to speculate that TLR2 could promote anti-tumoral T cell responses by providing costimulatory signals to T cells and prolonging cytokine mRNA half-life. This in turn can potentiate the response rate of other immune cell types, as shown for B cells and macrophages (27, 71). TLR ligands may also act on T cell subsets residing at barrier tissues, like tissue resident memory T cells.…”
Section: Discussionmentioning
confidence: 93%
“…It is therefore tempting to speculate that TLR2 could promote anti-tumoral T cell responses by providing costimulatory signals to T cells and prolonging cytokine mRNA half-life. This in turn can potentiate the response rate of other immune cell types, as shown for B cells and macrophages (27, 71). TLR ligands may also act on T cell subsets residing at barrier tissues, like tissue resident memory T cells.…”
Section: Discussionmentioning
confidence: 93%
“…It is therefore tempting to speculate that TLR2 could promote antitumoral T cell responses by providing costimulatory signals to T cells and prolonging cytokine mRNA t 1/2 . This in turn can potentiate the response rate of other immune cell types, as shown for B cells and macrophages (27,71). TLR ligands may also act on T cell subsets residing at barrier tissues, like tissue-resident memory T cells.…”
Section: Discussionmentioning
confidence: 99%
“…32,36 In vivo, TLR7-and influenza A-induced type I interferon signaling have been reported to suppress ILC2s. 36,53 Both stimuli also trigger IFNg, 55,56 but the interplay between both interferons has not been elucidated in the context of ILC2s. We found that type I interferons are crucial for IFN-g production by NK cells given that IF-NAR blockade markedly reduced IFN-g production.…”
Section: Discussionmentioning
confidence: 99%